Comparison of Outcomes in Patients with Malignant Pleural Efusion et Causa Breast Cancer Metastase Thought of Pleurodesis with Talc Poudrage and Talc Slurry at Dr. M. Djamil General Hospital, Padang, Indonesia - Muhammad Ryan SA; Muhammad Riendra; Yopi Triputra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Breast cancer accounts for about 50-65% of malignant pleural effusions. Talc pleurodesis is one of the definitive procedures for pleural effusions in which the route of administration is divided into poudrage and slurry. This study aimed to compare the differences of outcomes in malignant pleural effusion patients et causa breast cancer metastase who receive pleurodesis therapy with talc poudrage and talc slurry. Methods: This study has a cross-sectional design, which was conducted at Dr. M. Djamil General Hospital in May – July 2023. This study used medical records of patients diagnosed with malignant pleural effusion due to metastases of breast cancer at Dr. M. Djamil General Hospital Padang from January 2019 – July 2023. The outcomes assessed included drain production in 24 hours, drain release time, and in-hospital mortality. Results: In this study, 12 respondents who have talc poudrage and talc slurry pleurodesis were included. In the talc poudrage group, the mean of 24-hour drain production was 259.17 ± 46.79 ml, the mean of drain release time was 4.08 ± 0.66 days, and there was one respondent who died during hospitality. In the talc slurry group, the mean of 24-hour drain production was found to be more (420.83 ± 78.21 ml), drain release time was found to be much longer (5.67 ± 0.98 days), and 3 respondents died in hospital. The bivariate analysis found a significant difference between the 24-hour drain production and drain release time of patients who underwent talc slurry and talc poudrage meanwhile there was no difference in hospital mortality. Conclusion: Talc poudrage has a better outcome than talc slurry regarding drain production and drain release time in patients with malignant pleural effusion due to metastases of breast cancer.